18.
[tex]a) \ (1\frac{3}{4})^{6}\cdot(\frac{2}{7})^{6} = (\frac{7}{4}\cdot\frac{2}{7})^{6} = (\frac{1}{2})^{6} = \frac{1}{64}\\\\b) \ (0,8)^{4}:(2\frac{2}{3})^{4} = (\frac{8}{10}:\frac{8}{3})^{4} = (\frac{8}{10}\cdot\frac{3}{8})^{4} = (\frac{3}{10})^{4} = \frac{81}{10000}\\\\c) \ (4\frac{1}{2})^{3}\cdot(-\frac{2}{3})^{3}\cdot(-2)^{3} = [\frac{9}{2}\cdot(-\frac{2}{3})\cdot(-2)]^{3} = (3\cdot2)^{3} = 6^{3} = 216[/tex]
[tex]d) \ (2\frac{1}{2})^{4}\cdot0,6^{4}:(-15)^{4} = [2,5\cdot0,6:(-15)]^{4} = [1,5:(-15)]^{4} = (-0,1)^{4} =\\\\=0,0001[/tex]